Ranking Road Safety Hazardous Location: A Case Study of Chhorepatan–Machhapuchhre Viewpoint Road Section - Rijal, Yubaraj; Baral, Nirmal Prasad; Duwadi, Sandip (Journal of Engineering and Sciences, 2023)
The importance of road safety, involving pedestrians, cyclists, motorcyclists, and drivers adhering to rules and strategies to prevent accidents and fatalities, is emphasized, especially in Nepal, where road fatalities remain a pressing issue. The study focuses on the Chhorepatan – Machhapuchhre Viewpoint Road Section, which faces increasing traffic density and hazards. It proposes a six-stage methodological framework, incorporating the Analytical Hierarchy Process (AHP) and field surveys, to rank hazardous locations based on safety parameters, resulting in a Safety Hazardous Index (SHI). The research aims to identify and prioritize key safety factors by correlating SHI values with crash records, potentially serving as a model for assessing road sections in similar conditions.